Species within the Bemisia tabaci (Hemiptera: Aleyrodidae) Complex in Soybean and Bean Crops in Argentina - Alemandri, V. (2012)
The White fly Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) is a cryptic species complex that contains some of the most damaging pests in tropical and subtropical regions. Recent studies suggested that this complex is composed of at least 24 distinct species. We use the approach from these studies to consider the identity of B. tabaci in Argentina. Previous studies have suggested the presence of a B. tabaci presumably indigenous to the Americas and referred to as the BR biotype in Argentina. We placed the entity referred to as the BR biotype within the B. tabaci cryptic species complex using whiteflies collected in soybean and bean crops in northern and central Argentina. The whiteflies were assigned using the mitochondrial cytochrome oxidase (mtCOI) gene. Four unknown haplotypes plus two Argentina sequences from GenBank formed a cluster that was basal to the rest of theNewWorld sequences. These sequences diverged from the consensus sequence across the range of 3.6 to 4.3%. Applying the species assignment rules of recent studies suggests that the individuals from Argentina form a separate species. A unknown haplotype fell within the New World putative species and formed a distinct cluster with haplotypes from Panama. These results suggest that Argentina has two indigenous species belonging to the B. tabaci cryptic species complex. Rather tan using mtCOI sequencing for all B. tabaci collected, a simple random amplifed polymorphic DNApolymerase chain reaction diagnostic was used and tested along with previously published primers designed to work specially with the BR biotype from Brazil. These primers were either unable to distinguish between the two indigenous members of the complex in Argentina or indicated a difference when none was evident on the basis of mtCOI sequence comparison.